2010
DOI: 10.3233/ch-2010-1265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ligaria cuneifolia catechin- and quercetin-enriched fractions on hemorheology and plasma cholesterol

Abstract: We tested the in vivo and the in vitro effects of both Ligaria cuneifolia catechin-and quercetin-enriched fractions on erythrocyte shape and deformability, and on plasma cholesterol level. For in vivo studies, adult male Wistar rats were randomized in three experimental groups which received intraperitoneally, once a day, 3 days: Control: saline solution (C; n = 6); catechin from L. cuneifolia, 0.60 mg/100 g body weight (CLc; n = 6), or quercetin from L. cuneifolia, 2.3 mg/100 g body weight (QLc; n = 6). For i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
0
7
1
1
Order By: Relevance
“…Compared to the increases in capillary tube hematocrit of ∼250% found after bradykinin and SNP administration [10], the increases in hematocrit found with insulin were, however, relatively small, indicating that there still seems potential for capillary blood volume to increase further. Of note, MCV was based on previous studies [24], [25]; while effects of insulin or hyaluronidase on MCV have not been reported, possible affects of a change in MCV on capillary tube hematocrit in the present study cannot be ruled out.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Compared to the increases in capillary tube hematocrit of ∼250% found after bradykinin and SNP administration [10], the increases in hematocrit found with insulin were, however, relatively small, indicating that there still seems potential for capillary blood volume to increase further. Of note, MCV was based on previous studies [24], [25]; while effects of insulin or hyaluronidase on MCV have not been reported, possible affects of a change in MCV on capillary tube hematocrit in the present study cannot be ruled out.…”
Section: Discussionmentioning
confidence: 58%
“…where MCV is the mean corpuscular volume in rats (±70 um 3 ) [24], [25]. Using frame by frame playback RBC flux in a capillary was determined, at least 5 times per measurement, by counting the number of RBCs to pass through a reference point in 1 second.…”
Section: Methodsmentioning
confidence: 99%
“…Estos cambios podrían deberse a la interacción de QLc o de catLc con la membrana eritrocitaria y a una disminución del volumen eritrocitario. Estos resultados sugieren que otro componente de Lc sería el responsable del descenso de Co plasmático observado (23).…”
Section: Dosis Crecientes Deunclassified
“…In folk medicine, the infusion of these plants are used as hypotensive and to reduce excess cholesterol. Also, their anti-carcinogenic, anti-diabetic and anti-HIV activities have been reported (Dominighini et al, 2010;Fernandez et al, 1998). Tripodanthus fl agellaris is used mainly as cardioactive drug in Cuyo region (Argentina) (Del Vitto et al, 1997;Fusco et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…There are some studies on the biological activities of L. cuneifolia and T. fl agellaris (Fusco et al, 2001;Fusco et al, 2004;Fusco et al, 2010;Ferrero et al, 2006;Dominighini et al, 2010). Few researchers have reported antibacterial activity of Loranthaceae species (Varela et al, 2001;Ukwueze et al, 2013).…”
Section: Introductionmentioning
confidence: 99%